Liquid chromatographic and spectrophotometric methods for the determination of erythromycin stearate and trimethoprim in tablets - Sonia T. Hassib; Awatef E. Farag; Ehab F. Elkady (Faculty of Pharmacy, Cairo University, 2011)
Simple, accurate and precise reversed-phase liquid chromatographic (LC) and spectrophotometric methods have been developed and validated for the determination of erythromycin stearate (ERS) and trimethoprim (TMP) in mixture. In LC method, chromatographic separation was achieved on a Symmetry® Waters C18 column (150 × 4.6 mm, 5 μm) based on isocratic elution using a mobile phase consisting of potassium dihydrogen phosphate buffer pH (9):acetonitrile:water (25:100:50, v/v/v) at a flow rate of 1.6 ml min−1 with UV detection at 210 nm for ERS and 280 nm for TMP. Besides, two spectrophotometric methods were applied after reaction with perchloric acid (12 M) which gives a colored product with ERS. Then, the spectral interference between the colored product of ERS and TMP was resolved by either ratio spectra derivative spectrophotometry in the first spectrophotometric method or chemometric techniques, namely classical least-squares (CLS), principal component regression (PCR) and partial least-squares regression (PLS) in the second spectrophotometric method. The results were statistically compared using one-way analysis of variance (ANOVA). The methods developed were satisfactorily applied to the analysis of the pharmaceutical preparation containing the two drugs and proved to be specific and accurate for the quality control of the cited drugs in pharmaceutical dosage forms.